Milling S2-Glass and Basalt Fiber Composites: A Comprehensive Damage Analysis - Unegbu, H. C.O.; Yawasa, Danjuma S.; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Jurnal Rekayasa Mesin, 2024)
This research provides a comprehensive analysis of the machining behavior and damage mechanisms of S2-glass and basalt fiber composites during milling. Both materials, known for their high-performance applications, present distinct challenges due to their anisotropic and heterogeneous properties. The study investigates surface roughness, delamination, fiber pull-out, and cutting forces under a range of spindle speeds, feed rates, and depths of cut. Finite Element Analysis (FEA) was employed to simulate stress distributions at the fiber-matrix interface, complementing the experimental data. Results indicate that basalt fiber composites are significantly more prone to surface roughness, delamination, and fiber pull-out compared to S2-glass composites, especially at higher spindle speeds and feed rates. Elevated cutting forces in basalt composites were strongly correlated with increased damage, whereas S2-glass composites exhibited greater resilience to machining-induced stress, allowing for more aggressive cutting with less risk of surface degradation. The FEA simulations validated these experimental findings, highlighting the critical role of stress concentration at the fiber-matrix interface in damage propagation. These insights underscore the importance of optimizing machining parameters for brittle composites like basalt and provide valuable guidelines for enhancing surface quality and structural integrity in industrial applications involving fiber-reinforced composites.